Peran Serta Masyarakat dalam Pengelolaan Instalasi Pengolahan Air Limbah (IPAL) Komunal di Kabupaten Kampar - Dariyatmo Dariyatmo; Yusni Ikhwan Siregar; Sofia Anita (Jurnal Zona, 2024)
Communal IPAL is a sanitation infrastructure in the form of a building that is used to process community waste which is used communally. Communities play an important role in communal wastewater treatment plants (IPAL) because they are the users and owners of the wastewater sources that must be treated. This research aims to analyze the factors that influence Community Participation in the management of Communal Waste Water Treatment Plants (IPAL) in Kampar Regency. This research is quantitative with an analytical cross-sectional study design (Analytical Cross Sectional Study). The data in this research is primary data obtained by distributing questionnaires. The variables studied were the dependent variable (community participation in managing the Communal IPAL) and the independent variable (knowledge, education, economy and government support). The research results show that there is a significant relationship between economic knowledge (Pvalue 0.002) and government support (Pvalue 0.02) with community participation in the management of Communal IPAL in Kampar Regency. and there is no relationship between education and community participation in the management of Communal IPAL in Kampar Regency (Pvalue 0.069). It is hoped that the community can actively participate in the operation and maintenance of the communal IPAL and that the government will always accompany the community using the communal IPAL in operational and maintenance activities.